Leveling the Research Playing Field: Decolonizing Global Health Research Through Web-Based Platforms - Rajeev Seth; Baldeep K Dhaliwal; Emily Miller; Tyler Best; Alexis Sullivan; Betty Thankachen; Yawar Qaiyum; Anita Shet (Journal of Medical Internet Research, 2023)
Global health research has traditionally been rooted in colonialism, with some investigators in high-income countries leading and managing research and investigators in low- and middle-income countries serving as implementing partners. The Community Health Worker-Led Intervention for Vaccine Information and Confidence (CIVIC) Project, conducted in India and led jointly by India- and US-based investigators, leveraged web-based platforms to facilitate a more horizontal, inclusive, and balanced approach to partnerships between researchers and the community. Using web-based platforms to conduct research was found to be an effective strategy to engage researchers at all levels and combat systemic barriers associated with in-person activities such as power, economic, social, and gender dynamics. Connecting online for research meetings created a more equitable environment for community members to engage meaningfully with research. Further, by conducting research through web-based platforms, we found that we were able to strengthen the diversity of participants, provide a space for more marginalized groups to speak up, and minimize logistical barriers to attendance. Harnessing web-based approaches in research provides a pathway toward opportunities to promote equity and contribute to the decolonization of global health spaces.